Schumpeter, Marx et Walras. Entrepreneur et devenir du capitalisme - Sophie Boutillier; Dimitri Uzunidis (Revue Interventions Économiques)
Schumpeter invented the entrepreneur to conceptualize the innovation act that the model of pure economy of Walras was unable to explain. In doing so, he converged to Marx. In this paper, we propose to come back to the two nodal economists, Walras and Marx, who marked the work of Schumpeter. Admiring the work of the one and of the other, Schumpeter aimed to go further. Did he really succeed to do so? On the one hand, in Schumpeter’s work, the entrepreneur remains an abstract entity, although he had the ambition to find a solution to the Walrasian abstraction. On the other hand, he could only observe the bureaucracy - through the concentration process - of the capitalist production which had become the norm of managerial capitalism.